Diurnal variability and long-term daily trends in future offshore wind energy over the Mediterranean Sea from CMIP6 EC-Earth3 projections - Aydogan, Burak; Islek, Fulya; Ayat, Berna (ELSEVIER, 2026)
This study examines the changes in the future offshore wind energy resources in the Mediterranean Sea with the goal of contributing to the region's sustainable energy development. The validation of the downscaled CMIP6 ECEarth3 model demonstrated the reliability of bias-corrected model data to reproduce historical wind conditions. Future changes (FCs) in wind energy resources are characterised by an overall decrease, with the most pronounced decreases observed under the high-emissions SSP5-8.5 scenario. Seasonal FCs in WPD reveal more notable declines, indicating that climate change signals are more robust on a seasonal scale. According to both the annual and seasonal analyses, higher FCs are found in the western Mediterranean compared to the eastern basin. Even though there is a general decline in average WPD, the Gulf of Lion, Aegean Sea, and Alboran Sea will likely remain significant in wind resources throughout the 21st century. This study provides a novel calendar day trend analysis and investigates the evolving diurnal variability of WPD under future climate scenarios, utilizing high-resolution, bias-corrected EC-Earth3 projections. The diurnal variability of WPD is anticipated to increase, resulting in enhanced contrast between daily maxima and minima. Analysis of the long-term daily trends in WPD over the 151 years reveals that statistically significant changes occur on up to 86% of the calendar days, indicating that wind energy behaviour is changing over a long-time scale.
Keywords: Mediterranean; Wind power projection; Expected changes; SSP scenarios; CMIP6; Diurnal variation; EC-Earth3; POWER; CIRCULATION; EXPANSION; SPEED; Energy & Fuels